Theoretical Review Study: Peran Dan Fungsi Manajemen Dalam Mengelola Bisnis Online Shop - Amelia Suci Pertiwi; Dety Mulyanti (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
The role and function of management in managing a business which means managing an online shop business with management is to build good business performance, increase sales, and expand the market. Goals that can be achieved through online shop business management include: improving the quality of products and services, expanding marketing networks through social media and cooperation with other parties, building a loyal consumer community, using the right marketing mix, and utilizing technology to shape the entrepreneurial spirit through online shop business. The purpose of this theoretical review study is to find out how the role and function of management in managing an online shop business. The method used is a theoretical review study by analyzing and comparing existing theories. The result of this theoretical review study is its role and function, namely marketing strategy, human resource management, financial management, and business model canvas. In developing an online shop business, a canvas business model analysis can be carried out and the use of SWOT analysis techniques to determine the advantages, weaknesses, opportunities, and threats in the business currently owned. It can be concluded that the role of management is very important in the business world both offline and online. With the management can support parts of marketing, production, accounting, finance, and human resource management. For someone who is running an online shop business, it is also necessary to improve the quality of service to customers in selling quality products. So that in its implementation, it is necessary to carry out a business strategy to analyze the advantages, weaknesses, opportunities, and threats in the business currently owned.